Simulation and Feedback in Health Education: A Mixed Methods Study Comparing Three Simulation Modalities - Lauren Tait; Kenneth Lee; Rohan Rasiah; Joyce M. Cooper; Tristan Ling; Benjamin Geelan; Ivan Bindoff (MDPI AG, 2018)
Background. There are numerous approaches to simulating a patient encounter in pharmacy education. However, little direct comparison between these approaches has been undertaken. Our objective was to investigate student experiences, satisfaction, and feedback preferences between three scenario simulation modalities (paper-, actor-, and computer-based). Methods. We conducted a mixed methods study with randomized cross-over of simulation modalities on final-year Australian graduate-entry Master of Pharmacy students. Participants completed case-based scenarios within each of three simulation modalities, with feedback provided at the completion of each scenario in a format corresponding to each simulation modality. A post-simulation questionnaire collected qualitative and quantitative responses pertaining to participant satisfaction, experiences, and feedback preferences. Results. Participants reported similar levels satisfaction across all three modalities. However, each modality resulted in unique positive and negative experiences, such as student disengagement with paper-based scenarios. Conclusion. Importantly, the themes of guidance and opportunity for peer discussion underlie the best forms of feedback for students. The provision of feedback following simulation should be carefully considered and delivered, with all three simulation modalities producing both positive and negative experiences in regard to their feedback format.